Pengaruh Kualitas Produk, Persepsi Harga dan Promosi terhadap Keputusan Pembelian Frozen Food di UD Family Food (Lembaga Pengembangan Kinerja Dosen, 2025)
This study was conducted with the aim of examining the extent to which product quality, price perception, and promotion influence consumer decisions in purchasing frozen food products at the MSME UD Family Food. The approach employed was quantitative, using multiple linear regression analysis. A total of 100 respondents were selected through purposive sampling, with questionnaires serving as the primary instrument for data collection. The independent variables in this study consist of product quality (X1), price perception (X2), and promotion (X3), while the dependent variable is purchase decision (Y). The findings reveal that both partially and simultaneously, the three independent variables have a significant effect on purchase decisions. Among these, product quality emerged as the most dominant factor, surpassing the influence of price perception and promotion. The R Square value obtained was 0.761, indicating that 76.1% of the variation in purchase decisions can be explained by these three variables, while the remaining percentage is influenced by other factors not examined in this study. In conclusion, product quality, price perception, and promotion are crucial elements that influence consumer decisions in choosing frozen food products at UD Family Food. These findings are expected to provide valuable insights for MSME practitioners in designing more effective marketing strategies to enhance competitiveness and increase sales volume.